2017
DOI: 10.1103/physrevb.95.115409
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electronic properties of monolayer group III monochalcogenides

Abstract: We investigate the structural, mechanical, and electronic properties of the two-dimensional hexagonal structure of group III-VI binary monolayers, MX (M = B, Al, Ga, In and X = O, S, Se, Te) using first-principles calculations based on the density functional theory. The structural optimization calculations and phonon spectrum analysis indicate that all of the 16 possible binary compounds are thermally stable. In-plane stiffness values cover a range depending on the element types and can be as high as that of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
175
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 328 publications
(209 citation statements)
references
References 61 publications
23
175
2
Order By: Relevance
“…These experiments have identified two main photoluminescence lines, interpreted 30 as a lower energy transition between bands dominated by s and p z orbitals (A-line) and hot luminescence, involving holes in a deeper valence band based on p x and p y orbitals (B-line). The band structure analysis of mono-and few-layer InSe [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] has revealed that the conduction and valence band edges near the Γ-point are non-degenerate, being dominated by s and p z orbitals of both metal and chalcogen atoms. Combined with the opposite z → −z (mirror reflection) symmetry of conduction and valence bands, this determines that the transition across the principal band gap has a dominantly electric dipole-like character, coupled to out-of-plane polarized photons.…”
Section: Introductionmentioning
confidence: 99%
“…These experiments have identified two main photoluminescence lines, interpreted 30 as a lower energy transition between bands dominated by s and p z orbitals (A-line) and hot luminescence, involving holes in a deeper valence band based on p x and p y orbitals (B-line). The band structure analysis of mono-and few-layer InSe [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] has revealed that the conduction and valence band edges near the Γ-point are non-degenerate, being dominated by s and p z orbitals of both metal and chalcogen atoms. Combined with the opposite z → −z (mirror reflection) symmetry of conduction and valence bands, this determines that the transition across the principal band gap has a dominantly electric dipole-like character, coupled to out-of-plane polarized photons.…”
Section: Introductionmentioning
confidence: 99%
“…In the infrared active modes, two N atoms in the same square move in the same direction while in the Raman active modes, the opposite is true. The E u branches with the highest frequencies have striking similarity to the Mexican hat dispersion of the valence band edge of so-structures [45]. Hence, the Mexican hat dispersion that appears both in the electronic and phononic band structures can be interpreted as a fundamental property of interactions in the so geometry.…”
Section: A Dynamical Stability Symmetries Of Phononsmentioning
confidence: 79%
“…This defect motivated the search for novel 2D materials. In recent years, some 2D materials, including, but not limited to, black phosphorene (BP), 7 transition-metal dichalogenides (TMDs), [8][9][10] monolayer group IV, 11 monolayer group V, 12,13 and monolayer group III monochalcogenides, 14,15 have been explored. Due to the high carrier mobility and direct band gap, BP is emerging as a contender in the eld of 2D materials.…”
Section: Introductionmentioning
confidence: 99%